Assessment of sleep quality and daytime sleepiness in German national ice hockey players preparing for the world championship - Hof zum Berge, A.; Loch, F.; Schwarzenbrunner, K.; Ferrauti, A.; Meyer, T.; Pfeiffer, M.; Kellmann, M. (German Journal of Exercise and Sport Research, 2021)
Objectives were to examine subjective sleep quality and daytime sleepiness of the German ice hockey junior national team prior to the world championship to identify athletes of concern and areas of optimization with the intention of equally preventing injury and enhancing performance. Methods: Twenty-one athletes (Mage= 18.5± 0.6 years, Mheight= 181.7± 4.3cm, Mweight= 81.4± 7.1kg), playing for national (n= 13) and international (n= 8) home clubs, answered the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS) before training camp (T1, day 1) and prior to tournament (T2, day 11). Results; Overall, 9 players at T1 and 7 at T2 were identified as bad sleepers (PSQI > 5), while high sleepiness (ESS > 10) was found for 6 athletes at each measurement time. Group means and standard deviations reduced descriptively for PSQI (T1= 5.38± 2.31, T2= 4.57± 2.36) and ESS (T1= 9.24± 3.74, T2= 8.48± 3.28). Tendential differences were visible for PSQI in international-based players (Z= -1.7, p= 0.09) and ESS in first-national-league players (Z= -1.73, p= 0.08) over time. Higher PSQI values for international-based players (6.25± 2.6) were found compared to first-national-league (5.83± 1.60) and lower-league players (4.00± 2.08), with large effect sizes for lower-league compared to international (d= 0.95) and national players (d= 0.98) at T1 and small effect sizes compared to first-league players (d= 0.24) at T2. Conclusion; Findings emphasize great vulnerability and individuality and underline the importance of intraindividual sleep monitoring to meet the requirements needed to equally obtain health and enhance overall performance.